ANALISIS PERBEDAAN TINGKAT KEPUASAN ANTARA PASIEN PESERTA PKMS GOLD DAN PKMS SILVER PADA UNIT RAWAT INAP RSUD DR. MOEWARDI SURAKARTA - Rosalinda Trajuningtyas; Ayun Sriatmi; Putri Asmita Wigati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2015)
Since 2008 the Government has introduce health insurance program called Jaminan Kesehatan Masyarakat (Jamkesmas) to increase accessibility of the poor and unable for health services. Besides Jamkesmas, there are regional health insurance program that guarantees the poor who are not included in the quota of Jamkesmas program called Jaminan Kesehatan Daerah (Jamkesda). One region that has been successful to running this program is Surakarta, Central Java with its regional health insurance program called Pemeliharaan Kesehatan Masyarakat Surakarta (PKMS). PKMS have two type of membership namely PKMS Gold to the poor and PKMS to non-poor criteria. PKMS is one of manage care organization in Indonesia. The quality of services always be question in managed care, which is it closely related to patient satisfaction. Dr. Moewardi hospital is one of the third level provider that corporate with. In-patient visit in that hospital by PKMS participants is the biggest from last three years. Based on preliminary survey, PKMS Gold participants are more satisfied than PKMS Silver’s according Linder-Pelz theory of satisfaction. This research is quantitative model with satisfaction survey using questionnaire. Total subjects are 90 respondents with 22 PKMS Gold holders and 68 PKMS Silver holders. Respondent taking with a simple random sampling method. Data analysis using univariat analysis and bivariat analysis Mann Whitney U-Test. Research shows there are different levels of satisfaction between PKMS Gold and PKMS Silver participants in Humaneness and Pleasentness of Surrounding dimension. Suggestions for Dr. Moewardi hospital are provide media for information and criticism-advise, improve service from staff, recruit staff of paramedic, and improve facility management in the hospital.